What do we know about war? - Mitchell, Sara McLaughlin; Vasquez, John A. (Rowman & Littlefield, 2021)
Territory and Contentious Issues / Paul R. Hensel and Hein Goemans -- Dyadic Power Distributions and War: Theories, Evidence, and Recommendations for Assessing the Roles of Parity and Preponderance / Daniel S. Morey and Kelly M. Kadera -- Deterrence Theory and Alliance Politics / Michael R. Kenwick and Roseanne W. McManus -- Arms Races / Susan G. Sample -- Rivalries and Crisis Bargaining / Seden Akcinaroglu and Elizabeth Radziszewski -- Nuclear Weapons / Matthew Fuhrmann -- Outcomes and Consequences of War / Stephen L. Quackenbush -- The Liberal Peace / Michael Mousseau -- The Territorial Peace: Current and Future Research / Douglas M. Gibler and Steven V. Miller -- The Peace Puzzle: Understanding Transitions to Peace / Paul F. Diehl, Andrew P. Owsiak, and Gary Goertz -- Conflict Management of Territorial and Maritime Disputes / Emilia Justyna Powell and Krista E. Wiegand -- Cyber War / Brandon Valeriano, Ryan C. Maness, and Benjamin Jensen -- The Environment and Conflict: Water Wars / Sara McLaughlin Mitchell and Yufan Yang -- Leaders and War / Scott Wolford -- War Financing and Foreign Debt / Rosella Cappella Zielinski and Paul Poast -- Trends in Interstate Conflict / Bear F. Braumoeller -- Some Brief Observations on the Contemporary Study of War / William R. Thompson -- War and The Orient Express / Andrew P. Owsiak and Douglas Atkinson -- What Do We Know about War? / Sara McLaughlin Mitchell and John A. Vasquez.